Thermal physiology and thermoregulatory behaviour exhibit low heritability despite genetic divergence between lizard populations. Issue 1878 (9th May 2018) - Logan, Michael L.; Curlis, John David; Gilbert, Anthony L.; Miles, Donald B.; Chung, Albert K.; McGlothlin, Joel W.; Cox, Robert M.
Abstract : Ectothermic species are particularly sensitive to changes in temperature and may adapt to changes in thermal environments through evolutionary shifts in thermal physiology or thermoregulatory behaviour. Nevertheless, the heritability of thermal traits, which sets a limit on evolutionary potential, remains largely unexplored. In this study, we captured brown anole lizards ( Anolis sagrei ) from two populations that occur in contrasting thermal environments. We raised offspring from these populations in a laboratory common garden and compared the shape of their thermal performance curves to test for genetic divergence in thermal physiology. Thermal performance curves differed between populations in a common garden in ways partially consistent with divergent patterns of natural selection experienced by the source populations, implying that they had evolved in response to selection. Next, we estimated the heritability of thermal performance curves and of several traits related to thermoregulatory behaviour. We did not detect significant heritability in most components of the thermal performance curve or in several aspects of thermoregulatory behaviour, suggesting that contemporary selection is unlikely to result in rapid evolution. Our results indicate that the response to selection may be slow in the brown anole and that evolutionary change is unlikely to keep pace with current rates of environmental change.